Resistance behaviours towards mobile commerce applications: A study among mobile users - Hew, Jun Jie (2024)
Ever since its emergence, mobile commerce (m-commerce) has disrupted many business industries via various types of m-commerce applications. However, a significant portion of Malaysian mobile users still does not accept or adopt m-commerce applications. Moreover, the same phenomenon is also reported across different nations, which strongly suggests that the resistance to m-commerce applications is a contemporary worldwide issue that deserves immediate attention. To explain the complicated resistance behaviours of mobile users (i.e., rejection, postponement, or opposition) towards m-commerce applications, this study builds a holistic framework named the M-Commerce Applications Resistance Theory (MOCART) by integrating mobile users’ information privacy concerns (MUIPC) and mobile technostress, which are derived from the Communication Privacy Management Theory and Technostress Theory respectively, into the Innovation Resistance Theory (comprises passive innovation resistance and active innovation resistance). Subsequently, the MOCART is empirically verified with 1,050 responses that were collected through a quota sampling technique. The empirical results are supportive of the rigorously established MOCART, suggesting that MUIPC, mobile technostress, and passive innovation resistance are the antecedents of active innovation resistance, which consequently drives all three types of resistance behaviour towards m-commerce applications. Given these outcomes, it is confident that the MOCART could explain three distinct forms of resistance behaviour exhibited by mobile users who do not adopt m-commerce applications. Besides, the MOCART could serve as a universal theory to explain the resistance behaviours towards any m-commerce applications. Accordingly, and broadly speaking, the MOCART has successfully advanced the current state of knowledge in the research disciplines of innovation resistance and m-commerce applications. Besides, the MOCART offers several practical implications. Generally, to inhibit the resistance behaviours towards m-commerce applications, practitioners and government policymakers should strive to minimise the resistant mobile users’ active innovation resistance by reducing its drivers namely MUIPC, mobile technostress, and passive innovation resistance.